Workload and quality of life of medical doctors in the field of oncology in Germany: a survey of the working group Quality of life of the AIO for the study group of internal oncology - Hipp, Matthias; Pilz, Lothar R.; Hofheinz, Ralf-Dieter (Oncology research and treatment, 2015)
Background: An increasing number of surveys have investigated professional stress and satisfaction among oncologists. Coevally, structural development has changed the oncological working environment. This survey investigated the quality of life and job stress among German oncological physicians. Methods: A 48-item questionnaire, which included the ‘Stress questionnaire of physicians and nurses' (FBAS), was developed by the ‘Quality of life' working group of the Internal oncology study group (AIO), and distributed anonymously at the annual meeting of the AIO working group in 2010. Descriptive statistics as well as univariate and multivariate analysis were performed. Results: 261 oncologists, mostly male (64%), older than 40 years (38%), and medical specialists (78%), took part in the survey. ‘Structural conditions' were identified as causing the highest mean stress levels, followed by ‘professional and private life'. Female participants showed a significantly lower global quality of life than male participants (p = 0.020). ‘Structural conditions' induced more stress among younger oncologists < 50 years old (p < 0.001). Qualification status was influenced by gender (p < 0.001); the multivariate analysis described the dependence of gender (p = 0.0045), working situation (p = 0.0317) and global stress (p = 0.0008). Conclusion: Structural conditions, age younger than 50 years and female gender were identified as stress risk factors among the AIO members, and showed that job stress is present in German oncology. Further research is warranted to develop evidence-based intervention strategies.